The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.physleta.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Standing electromagnetic solitons in degenerate relativistic plasmas

Abstract: The existence of standing high frequency electromagnetic (EM) solitons in a fully degenerate overdense electron plasma is studied applying relativistic hydrodynamics and Maxwell equations. The stable soliton solutions are found in both relativistic and nonrelativistic degenerate plasmas.A significant amount of recent publications describe electromagnetic (EM) waves in relativistic plasmas and majority of them discuss possible roles of these waves in different astrophysical phenomena. Highly relativistic plasma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Nonlinear 1D relativistic solitons were studied analytically in Refs. [25][26][27] and numerically in Refs. [28,29].…”
Section: Introductionmentioning
confidence: 98%
“…Nonlinear 1D relativistic solitons were studied analytically in Refs. [25][26][27] and numerically in Refs. [28,29].…”
Section: Introductionmentioning
confidence: 98%
“…In a series of papers [5]- [8], where authors examined the nonlinear character of interactions of plasma waves and high frequency EM waves it was found that ✩ Fully documented templates are available in the elsarticle package on CTAN.…”
Section: Introductionmentioning
confidence: 99%
“…In the present paper, we apply the fluid-Maxwell model developed in [5], [7] to study the possibility of FI of intense narrow electromagnetic pulse L ⊥ << L (where L and L ⊥ are the characteristic longitudinal and transverse spatial dimensions of the field, respectively) in the transparent degenerate electron plasma to show the possibility of FI in relativistic degenerate plasma embedded in the field of arbitrary strong EM radiation.…”
Section: Introductionmentioning
confidence: 99%
“…For discussion on the formation and features of EM soliton, the Maxwell and fluid equations should be solved. A multiple scales technique is used to solve the fluid-Maxwell equations in cold plasma [10][11][12][13][14]. Kuehl and Zhang [15] have expressed the creation of bright and dark EM soliton in weakly relativistic approximation.…”
Section: Introductionmentioning
confidence: 99%